2003
DOI: 10.1136/bjsm.37.5.410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strength and proprioception training on eversion to inversion strength ratios in subjects with unilateral functional ankle instability

Abstract: Objectives: To examine the effect of six weeks of strength and proprioception training on eversion to inversion isokinetic strength ratios (E/I ratios) in subjects with unilateral functional ankle instability. Methods: Thirty eight subjects were randomly assigned to one of four treatment groups: strength training (S); proprioception training (P); strength + proprioception training (B); control (C). Isokinetic strength was tested before and after training using a Kin Com 125 automatic positioning isokinetic dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
108
2
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(121 citation statements)
references
References 35 publications
3
108
2
8
Order By: Relevance
“…This study used Thera-Band Ò elastic bands to perform inversion, eversion, dorsiflexion and plantar flexion as well as perturbation during a single limb balance exercise over a four week, 12 session rehabilitation program. There were no differences in eversion/ inversion isokinetic strength between subjects with ankle instability and healthy control subjects [86]. In contrast to this study, Docherty et al [87,88] found increased dorsiflexion and eversion strength following six weeks of strength training.…”
Section: Rehabilitationcontrasting
confidence: 49%
See 1 more Smart Citation
“…This study used Thera-Band Ò elastic bands to perform inversion, eversion, dorsiflexion and plantar flexion as well as perturbation during a single limb balance exercise over a four week, 12 session rehabilitation program. There were no differences in eversion/ inversion isokinetic strength between subjects with ankle instability and healthy control subjects [86]. In contrast to this study, Docherty et al [87,88] found increased dorsiflexion and eversion strength following six weeks of strength training.…”
Section: Rehabilitationcontrasting
confidence: 49%
“…To address muscle weakness and function, Kaminski et al [86] intervened with strength training and proprioceptive training on subjects with ankle instability and a history of recurrent sprains. This study used Thera-Band Ò elastic bands to perform inversion, eversion, dorsiflexion and plantar flexion as well as perturbation during a single limb balance exercise over a four week, 12 session rehabilitation program.…”
Section: Rehabilitationmentioning
confidence: 99%
“…If the ankle musculature is strong, the athlete can withstand greater force before an injury is sustained. In addition to decreasing ankle injuries, strengthening lower leg muscles will help prevent injuries [3].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in lower extremity kinematics during gait [16][17][18][19] and jump landings 20,21 also are evident in individuals with CAI, whereas strength deficits are controversial. [22][23][24][25][26] It is unclear whether these deficits and alterations occur in individuals before or after an initial ankle sprain.…”
mentioning
confidence: 99%